Unconventional delivery of inhaled nitric oxide during endoscopic laryngeal tracheal reconstruction in a child with pulmonary arterial hypertension: A case report. Issue 11 (17th September 2019) - Lee, Jennifer J.; Kazim, Robert; Jang, Minyoung; Grunstein, Eli
Abstract: Endoscopic laryngeal tracheal reconstruction was performed on a child with glottic stenosis and pulmonary arterial hypertension. The surgical repair was performed while delivering inhaled nitric oxide via the ventilating port of a suspension laryngoscope with the patient maintaining spontaneous respirations. The surgery was accomplished without complications.